Framework for Demystifying M2M Spectrum Regulation - Khosla, Arpit; C.B., Anuradha (Journal of Telecommunications and the Digital Economy, 2018)
The evolving M2M landscape not only cuts across diverse verticals but also embraces a range of networks and devices. This diversity leads to varied and dynamic requirements, which make regulatory policy formulation a daunting challenge. In this fast-changing environment, of all the regulatory policy dimensions, the one that confounds the regulator the most is the regulation of Spectrum. The typical dilemmas that regulators face in the domain of spectrum can be boiled down to questions like- Is the unlicensed band sufficient to maintain scalability with QOS for various use cases, Does the demand and other requirements warrant a separate licensed band for M2M etc. As expected, there is no panacea for spectrum access regulation. This can be attributed to the fact that the technical requirements (for example data throughput, reliability, range, and output power etc.) vary dramatically across the spectrum of use cases. To exacerbate the confusion in sizing up the varied and fast-changing technical requirements, a regulator is also expected to align its spectrum access policies to regulations and standards of other verticals. The advent of new Cognitive Radio, DSA, and other technologies, definitely don’t make the task of regulator any simpler.To us, the aforementioned situation implied that long-standing spectrum regulation principles and practices might have to go through an evolution. We do not claim that the basic objective of balancing spectrum demand, supply, and utilization will change. However, we believe that the way the regulator looks at these dimensions needs to change. To uncover this systematic change we researched the evolving practices of access network’s spectrum regulation across the globe, across verticals and across stakeholders. Then we tried to identify a pattern, which we crystallized into a simple framework. Our analysis is primarily based on secondary research.Via our paper, we wanted to share our perspective on the changed way in which regulator should look at Demand, supply, and utilization of Spectrum. In our paper, we propose a framework of factors, when considered, will help regulators look at this new world with an evolved lens. Using some selective samples our study also attempts at illustrating, as to how some of the proposed approaches (e.g. understanding spectrum demand) have been implemented by certain regulators. In certain sections of the paper, we also augment our view with specific data points from certain vertical industries. Finally, our study delves into earmarking and detailing the policy levers (e.g. Spectrum fees, sharing regulations, License Authorization Model) which can help regulator in reaching the aspired policy posture. The policy levers include both traditional and new age levers.Overall this framework attempts to demystify the spectrum policy regulation in the age of M2m/IOT. Additionally, our paper can also serve as a reference to many new players in M2M/IOT, who do not have a clear idea, as to what all ways, can a regulators spectrum policy impact their solution or their vertical.